تأثير استخدام استراتيجية العصف الذهني على مستوى تقدير الذات وتعلم بعض مهارات كرة السلة لدى تلاميذ المرحلة الثانوية (مجلة الواحات للبحوث والدراسات, 2022)
ملخصتهدف الدراسة إلى التعرف على تأثير استراتيجية العصف الذهني في تطوير مستوى تقدير الذات وتعلم بعض مهارات كرة السلة وقد استخدم الباحثان المنهج التجريبي بتصميم المجموعتين المتكافئتين،  واشتملت عينة الدراسة على (40) تلميذا من تلاميذ اولى ثانوي للفصل الدراسي الأول لعام ( 2019-2020)، وتم تقسيمهم بالتساوي إلى مجموعتين إحداهما تجريبية تدرس بنموذج العصف الذهني والثانية ضابطة تدرس بالنموذج التقليدي (العرض التوضيحي)، وكأداة جمع البيانات تم استخدام مقياس تقدير الذات واختبارات مهارية بكرة السلة، وقد أشارت  أهم النتائج إلى تحسن في مستوى تقدير الذات ومستوى اداء مهارات كرة السلة قيد البحث لكلا المجموعتين, مع تفوق كبير للمجموعة التجريبية التي استخدمت استراتيجية العصف الذهنيالكلمات المفتاحية : استراتيجية العصف الذهني، تقدير الذات، مهارات كرة السلة Abstract : The study aims to identify the impact of the brainstorming strategy in developing the level of self-esteem and learning some basketball skills. The researchers used the experimental method by designing the two equal groups, and the study sample included (40) students from the first secondary students for the first semester of the year (2019-2020). They were divided equally into two groups, one of them experimental, taught by the brainstorming model, and the second control group, taught by the traditional model (demonstration), and as a data collection tool, the self-esteem scale and basketball skill tests were used, and the most important results indicated an improvement in the level of self-esteem and the level of performance of basketball skills. The research for both groups, with a significant superiority of the experimental group that used the brainstorming strategy Key words:  Brainstorming strategy, self-esteem, basketball skills